Determinan Tingkat Kejahatan Properti (Property Crime) di Indonesia - Sukma, Putri Yulianda; Marta, Joan (Universitas Negeri Padang, 2024)
This study aims to find out and analyze how the Determinants of Property Crime Rate in Indonesia. This research is an effort to add to the existing literature on property crime research in developing countries, especially Indonesia. The type of data used in this study is secondary data sourced from the Central Statistics Agency (BPS) which is grouped into two parts, namely the dependent variable namely Property Crime and the independent variable consisting of Population Density, Education Level, Unemployment, Income Inequality and Police Power. This study used descriptive and inductive analysis. This study uses panel data regression analysis using the Fixed Effect Model (FEM) method with cross section of 34 Provinces in Indonesia and time series 2018 – 2021. The findings in the results of this study revealed that the variables of population density, education level, unemployment and police strength had a significant effect however, on the variable of income inequality did not have a significant effect on the level of property crime in Indonesia.